Utilization of Solar Energy for Electric Vehicle Charging and the Energy Consumption of Residential Buildings in Northern Cyprus: A Case Study - Kassem, Youssef; Gokcekus, Huseyin; Aljatlawe, Almukhtar (Engineering, Technology & Applied Science Research, 2023)
Solar energy represents an opportunity to facilitate the operation of Electric Vehicle (EV) charging stations and cover the energy demand of households, contributing to sustainability and reducing carbon emissions. In light of the emerging need for solar energy as a source of electricity generation for building and charging electric vehicles, this study aimed to assess the technical and economic feasibility of using photovoltaic (PV) systems to generate electricity for residential buildings and meet the changing needs of EVs to reduce energy demand on the grid. To achieve this objective, monthly solar radiation data were collected from the NASA power dataset to assess solar radiation levels in the region and determine the suitability and potential for harnessing solar energy for various applications. The results showed that northern Cyprus has exceptionally abundant and consistently stable solar energy resources. The daily energy for selected residential households and the GÜNSEL B9 and J9 electric cars was estimated to determine the capacity of the required PV systems. In addition, information was collected on the prices of solar panels, inverters, energy storage systems, etc., which were taken into account to evaluate the economic viability of the developed systems. The results demonstrate that the use of solar energy to charge EVs and meet the energy demands of households is technically viable and economically feasible. The use of electric cars offers nearly double the advantages compared to conventional fuel-powered ones, making them a more environmentally sustainable option.